A hybrid lithium storage mechanism of hard carbon enhances its performance as anodes for lithium-ion batteries. (30th June 2021) - Wang, Ke; Xu, Yaobin; Wu, Han; Yuan, Ruilong; Zong, Meng; Li, Yuan; Dravid, Vinayak; Ai, Wei; Wu, Jinsong
Abstract: Hard carbon is the most promising candidate material for lithium-ion batteries (LIBs) owing to its excellent cyclability and high stability. However, unlike graphite used in most of the commercial LIBs, most of the details of the electrochemical reaction mechanism in hard carbon remains unknown. Here, we report the dynamic structural evolutions of hard carbon in lithiation at the atomic scale by in-situ transmission electron microscopy. In the early stage of lithiation, Li-metal particles formed on the surface of hard carbon, while Li-ion intercalation was observed near the end of lithiation evidently by a slight lattice expansion of the graphitic layers in the hard carbon. These observations show that the Li-storage mechanism consist of a Li-metal surface absorption followed by the intercalation of Li-ions, namely a hybrid Li-metal and Li-ion storage mechanism. Furthermore, the optimized hard carbon (carbonized at 1000 °C for 2 h) delivers a high reversible capacity of 366.2 mAh g −1 at 50 mA g −1 for 100 cycles and 221.5 mAh g −1 at 1000 mAg −1 for 1000 cycles, respectively. Our investigation will provide insights in designing and fabricating more effective carbon-based nanostructured anode materials for the next generation LIBs with high capacity and cyclability. Graphical abstract: Image 1